Selective reduction of an Australian garnieritic laterite ore. (15th January 2019) - Yang, Jun; Zhang, Guangqing; Ostrovski, Oleg; Jahanshahi, Sharif
Highlights: Thermodynamic analysis outlines CO vol% of reducing gas for Ni & Co metallisation. Morphological & compositional changes occur to silicate minerals during reduction. Selective reduction obtains comparable Ni & Co metallisation but limits Fe to 20%. Increasing temperature after 740 °C weakens Ni, Co and Fe metallisation degree. Olivine recrystn traps more Ni, making it less reducible, & causes a drop in Ni yield above 740 °C. Abstract: Reduction of an Australian garnieritic laterite ore by different CO-CO2 gas mixtures was studied between 700 and 1000 °C. Two size ranges of the ore were examined: <53 μm and 53–200 μm. Metallic nickel, cobalt, and iron in reduced garnieritic laterite samples were leached out by a Br2 -CH3 OH solution; their concentrations in the solution were measured by inductively coupled plasma-optical emission spectrometry (ICP-OES) analysis to determine reduction degree. The changes in mineral phases, morphology and the chemical composition of these phases in the reduced ore were examined by XRD and SEM/EDS. It is confirmed that in this ore, nickel occurs with magnesium and iron as silicate isomorphisms including chlorite, talc and their derivative phases/particles (olivine and pyroxene). The BSE micrographs at high magnifications found Fe-Ni alloy was formed during reduction and its grains dispersed within silicate particles. The morphological and compositional observations indicate that numerous pores and cracks were generated in dehydroxylated chlorite, talc, and pyroxene particles, making nickel readily attacked by gases. Dense structures, however, were formed for olivine particles, rendering nickel inside difficult to reduce. Current study suggests that reduction temperature and reducing gas compositions are key factors for selective reduction. The optimal conditions for nickel and cobalt production from this garnieritic laterite by selective reduction can be mediated at 740 °C in 60% CO, at which satisfactory metallisation of 91% Ni and 94% Co in the particles <53 μm and 85% Ni and 99% Co in the particles 53–200 μm but less than 20% Fe were achieved.